Analisis Pengaruh Media PTC (Kentang, Tomat, dan Air Kelapa) terhadap Pertumbuhan Eksplan Jagung Manis - Novianty, Fitri; Nurmalasari, Intan Rohma (Universitas Garut, 2025)
This study aims to assess the effect of a combination of tissue culture media based on natural organic materials (potato, tomato, and coconut water) with sweet corn extract on the growth of sweet corn explants in vitro. The combination of sweet corn extract concentration (0, 50, and 100 g/L) and organic matter (0, 50, and 100 mL/L) was tested using a factorial completely randomized design (CRD) with three replications. The parameters observed included the time to grow adventitious buds, the percentage of adventitious buds, and the number of adventitious buds. The results showed that the combination of media did not significantly affect all parameters, but the combination of 100 g/L sweet corn extract with 100 mL/L organic matter tended to give better results, such as faster shoot growth time (18.25 HST). Independently, 100 g/L sweet corn extract gave a real effect on the highest percentage of adventitious shoot growth of 93%. This is due to the content of natural growth regulators, especially cytokinins, which encourage shoot growth. This study supports the potential use of natural organic materials as a tissue culture medium that is more environmentally friendly and economical, and shows the opportunity to develop sustainable tissue culture techniques based on local materials